2006
DOI: 10.1586/14737140.6.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Fertility-sparing therapy for young women with endometrial cancer

Abstract: Approximately 1600 women under the age of 40 will be diagnosed with endometrial cancer this year. For these women, preservation of fertility may be one of the most important factors when seeking treatment options. The objective of this article is to review the available literature on fertility-sparing therapy for young women with endometrial cancer. Patient selection, pretreatment testing, treatment regimens, response rates and pregnancy outcomes will be explored. Recommendations regarding this approach for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…The rate of coexisting ovarian malignancies and endometrial cancer in young women (<45 years) varies between 5 and 29% (12, 40–43). Therefore, this pre-treatment procedure is an essential step in the evaluation of endometrial lesion as suggested by several authors (44, 45). In our retrospective series, no ovarian malignancies were found.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of coexisting ovarian malignancies and endometrial cancer in young women (<45 years) varies between 5 and 29% (12, 40–43). Therefore, this pre-treatment procedure is an essential step in the evaluation of endometrial lesion as suggested by several authors (44, 45). In our retrospective series, no ovarian malignancies were found.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of one meta-analysis, contrast-enhanced MRI is better than non-contrast-enhanced MRI, CT scan or pelvis ultrasound in diagnosing the depth of myometrial invasion [22]. However, the accuracy of the current imaging techniques for excluding invasion of the inner half of the myometrium in cases of G1-EC is low [23]. Pelvic ultrasound is a less expensive tool but needs to be performed by an experienced physician to obtain accuracy similar to MRI [24].…”
Section: Controversial Topicsmentioning
confidence: 99%
“…This represents a different scenario and constitutes an absolute contraindication to fertility-sparing treatment. Several authors have proposed laparoscopy for diagnosis before EC treatment [8,6,23,30] in order to rule out the coexistence of an ovarian cancer or metastatic EC. However, limitations of laparoscopy include its application to cases with microscopic ovarian lesions only and the increased likelihood of adhesion formation, which would potentially decrease future fertility.…”
Section: Controversial Topicsmentioning
confidence: 99%
“…3 The younger group of women with endometrial carcinoma is frequently nulligravida with a history of infertility and a strong desire to preserve fertility. 4 Fortunately, the tumors in these patients tend to be well differentiated with no myometrial invasion and are associated with a favorable prognosis. 5 Because of the particularly good prognosis for premenopausal patients with endometrial cancer and because most of the young patients whose conditions are diagnosed with endometrial cancer also experience infertility, some attempts have been made to treat these patients with progestins rather than with surgery.…”
mentioning
confidence: 99%